2022
DOI: 10.1186/s12889-022-13273-y
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of factors associated with COVID-19 testing among people who inject drugs: missed opportunities for reaching those most at risk

Abstract: Background People who inject drugs (PWID) are vulnerable to SARS-CoV-2 infection. We examined correlates of COVID-19 testing among PWID in the U.S.-Mexico border region and described encounters with services representing potential opportunities (i.e., ‘touchpoints’) where COVID-19 testing could have been offered. Methods Between October, 2020 and September, 2021, participants aged ≥18 years from San Diego, California, USA and Tijuana, Baja Californ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 43 publications
(46 reference statements)
0
20
0
Order By: Relevance
“…In the meantime, we had completed formative research on barriers to COVID-19 testing and vaccination among PWID that led us to contemplate changes to our eligibility criteria. Specifically, we found that PWID who had been recently incarcerated or were homeless were significantly more likely to have undergone COVID-19 testing [ 13 ]. Consultations with our CSAB and in-depth interviews with PWID, supported with funding from the San Diego Center for AIDS Research, revealed that individuals in contact with the criminal justice system and homeless shelters were often subjected to mandatory (as opposed to voluntary) COVID-19 testing that had made them reluctant to engage in future voluntary testing [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the meantime, we had completed formative research on barriers to COVID-19 testing and vaccination among PWID that led us to contemplate changes to our eligibility criteria. Specifically, we found that PWID who had been recently incarcerated or were homeless were significantly more likely to have undergone COVID-19 testing [ 13 ]. Consultations with our CSAB and in-depth interviews with PWID, supported with funding from the San Diego Center for AIDS Research, revealed that individuals in contact with the criminal justice system and homeless shelters were often subjected to mandatory (as opposed to voluntary) COVID-19 testing that had made them reluctant to engage in future voluntary testing [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In May 2020, La Frontera investigators received additional funding to study the prevalence and correlates of SARS-CoV2 infection in the cohort. Preliminary data showing high SARS-CoV2 seroprevalence and low COVID-19 testing and vaccination uptake informed the design of the LinkUP pilot intervention [ 8 , 11 , 13 ], which was funded in September, 2021, through the RADx® Underserved Populations (RADx-UP) initiative of the National Institutes of Health (NIH), which was created “to ensure that all Americans have access to COVID-19 testing, with a focus on communities most affected by the pandemic” [ 40 ]. Since RADxUP funding was restricted to U.S. projects, LinkUP had the goal of enrolling 150 participants into a pilot RCT focused only on La Frontera cohort participants living in San Diego County.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations